ANATOMIC ASPECTS OF GERBERA PLANTS DURING ACCLIMATIZATION - Silva, Diogo Pedrosa Corrêa da; Paiva, Patrícia Duarte de Oliveira; Paiva, Renato; Alves, Eduardo; Porto, Jorge Marcelo Padovani; Reis, Michele Valquíria dos (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
Recently, there has been increasing interest in gerberas (Gerbera jamesonii), since its flowers present good durability and a range of colors that can satisfy the most demanding markets. The propagation, sexual and asexual, of gerbera presents a number of problems such as uneven seed germination and propagation of disease via clumps. Faced with these problems, tissue culture is an alternative for the production of healthy and large-scale seedlings. However, it is still necessary to improve the steps of the propagation to turn this process more efficient. The aim of this study was to analyze and characterize the aspects of gerbera leaves in different stages of acclimatization. Gerberas leaves were used at different stages of acclimatization: before acclimatization, 30 days after acclimatization in growth room and plants in full sunlight (field). Analyses were performed using scanning electron microscope in different leaf positions: adaxial and abaxial epidermis and perpendicular (Cryofracture). The results showed that during the acclimatization, the adaxial face presented a decrease in the number of stomata which was absent in plants in full sunlight. In the abaxial surface the formation of trichomes was observed during acclimatization and higher internal organization in leaves acclimatized and taken to the field, showing that the acclimatization of Gerbera jamesonii is a step of large changes for the plant.